Dietary knowledge, Attitude and Practices of Diabetes Patients at Services Hospital Lahore (International Journal of Applied Sciences and Biotechnology, 2017)
Introduction: Diabetes mellitus is growing fastly the world is witnessing.  The incidence of alarming concern to health care providers is rapidly rising. The main burden of this disease will fall on all developing countries. The number of diabetic patients will reach 300 million by the end of 2025 it is known through the estimation mostly developing countries will have such a dramatic and significant impacts. Methodology: The quantitative descriptive cross-sectional study design was used with convenient sampling (n=142) from Services Hospital Lahore. Using the questioner consist of 34 items data was analyzed through spss21 version descriptive analyses and the chi-square test with (p=